Theoretical Foundations of Corporate Governance and Board of Directors: A Systematic Literature Review - Maqdisa Putri Rafie; Irananda Sihombing; Fahmi Natigor Nasution; Iskandar Muda (Indo Publishing, 2025)
This study conducts a Systematic Literature Review (SLR) of corporate governance and board of directors research published between 2020-2025. Using data from leading academic databases including Scopus, Web of Science, and ScienceDirect, this research analyzes 20 peer-reviewed journal articles to identify the dominant theoretical framework, its conceptual and empirical relationship with governance mechanisms, and the challenges and benefits of its application. The analysis reveals that Agency Theory is the most frequently used theoretical framework (appearing 10 times), followed by Stakeholder Theory (8 times) and Resource Dependence Theory (4 times). Agency Theory conceptually links board characteristics such as independence, audit committees, and oversight structures to objectives of reducing information asymmetry and aligning managerial interests with shareholders. Empirical evidence shows that board independence and well-structured audit committees correlate positively with financial reporting quality and firm performance, although effectiveness is influenced by ownership structures, state control, and institutional contexts. The application of Agency Theory provides significant benefits in strengthening oversight and accountability, but faces practical challenges related to genuine board independence, resource constraints, and institutional barriers particularly in emerging markets. This study concludes that while Agency Theory provides a strong conceptual foundation, its practical success depends heavily on institutional quality, board capability, and the broader governance ecosystem.